(untitled) (Daffodil International University Journal of Science and Technology, 2011)
Steady two-dimensional Magneto hydrodynamic free convection flow with thermal radiation in the presence of magnetic field along a vertical flat plate is concerned in the present study. The fluid is taken to be gray, absorbing-emitting radiation. The non-linear governing equations have been transformed by the usual similarity transformation to a system of ordinary differential equations. These dimensionless similar equations are then solved numerically employing the Nachtsheim-Swigert shooting iteration technique along with sixth order Runge-Kutta integration scheme. Finally the effects of the pertinent parameters are examined. Keywords: MHD flow; radiation; magnetic field; kinematic viscosity; thermal diffusivity. DOI: http://dx.doi.org/10.3329/diujst.v6i2.9346 DIUJST 2011; 6(2): 55-62